1992
DOI: 10.1111/j.1530-0277.1992.tb01375.x
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive and Compulsive Characteristics of Craving for Alcohol in Alcohol Abuse and Dependence

Abstract: The purpose of this study was to quantify the extent to which subjective ratings of craving for alcohol in the alcohol-abusing or dependent person (herein, alcoholic) correlate with measurable and specific characteristics of obsessions and compulsions. The Yale-Brown Obsessive Compulsive Scale modified to reflect obsessionality and compulsivity specifically related to heavy drinking (Y-BOCS-hd) was used for this purpose. Highly significant correlations were found in the alcoholic population (n = 62) between su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
85
2
8

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 14 publications
1
85
2
8
Order By: Relevance
“…Based on the clinical similarities between the obsessive thoughts and compulsive behaviors of alcoholdependent subjects and those of patients with obsessive-compulsive symptomology, and evidence that serotonin reuptake inhibitors used in the treatment of OCD are also effective in inhibiting volitional drinking (Naranjo et al 1987) alcohol dependence has been compared to OCD (Modell et al 1992a(Modell et al , 1992b. Although the experience of compulsive "alcohol seeking" and "craving" reported by alcoholics long after withdrawal can not be equated with obsessive-compulsive symptomology, there may be some behavioral similarities.…”
Section: Endogenous Opioid Activity Has Been Associated With the Regumentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the clinical similarities between the obsessive thoughts and compulsive behaviors of alcoholdependent subjects and those of patients with obsessive-compulsive symptomology, and evidence that serotonin reuptake inhibitors used in the treatment of OCD are also effective in inhibiting volitional drinking (Naranjo et al 1987) alcohol dependence has been compared to OCD (Modell et al 1992a(Modell et al , 1992b. Although the experience of compulsive "alcohol seeking" and "craving" reported by alcoholics long after withdrawal can not be equated with obsessive-compulsive symptomology, there may be some behavioral similarities.…”
Section: Endogenous Opioid Activity Has Been Associated With the Regumentioning
confidence: 99%
“…Studies with OCD subjects have shown naloxone decreases obsessional doubt and compulsive behaviors at low doses (Insel and Pickar 1983;Keuler et al 1996) and decreases at higher doses (Sandyk 1987) in a small subgroup of subjects. Furthermore, opioid agents have been reported to affect stereotypic behavior observed in animals and humans, suggesting possible contributions by these neurotransmitter systems in obsessive-compulsive symptomology (Rapoport 1990, Rapoport et al 1992Stein et al 1994;Gietzen 1990;Dodman et al 1988).Based on the clinical similarities between the obsessive thoughts and compulsive behaviors of alcoholdependent subjects and those of patients with obsessive-compulsive symptomology, and evidence that serotonin reuptake inhibitors used in the treatment of OCD are also effective in inhibiting volitional drinking (Naranjo et al 1987) alcohol dependence has been compared to OCD (Modell et al 1992a(Modell et al , 1992b. Although the experience of compulsive "alcohol seeking" and "craving" reported by alcoholics long after withdrawal can not be equated with obsessive-compulsive symptomology, there may be some behavioral similarities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The latter does suffer from his/her condition in the very literal sense of this word (ibid.). However, the early studies on phenomenology and behaviour symptomatic of the craving for alcohol, performed at the end of the 1980s and beginning of the 1990s, immediately showed that the similarities between the two conditions were deeper than believed (Modell et al 1992a;Anton 2000). So deep were these similarities that the so-called obsessive-compulsive scale, the basic instrument used by psychiatrists to assess the severity of the obsessive-compulsive syndrome, as well as to plan its treatment and predict its outcome, could easily be adopted to assess the severity of alcohol-related problems and predict the outcome of their treatment (Modell et al 1992b).…”
Section: Of Psychological Alcohol Dependencymentioning
confidence: 99%
“…Tout d'abord, l'intensité du symptôme nécessaire pour que ce critère du DSM soit rempli pourrait être mieux définie. Dans les cas de dépendance à l'alcool, par exemple, certaines données laissent entrevoir des similitudes entre le craving et un processus d'intensité obsessionnel (Modell, Glaser, Cyr et Mountz, 1992). L'ajout d'une telle spécification aiderait à mieux illustrer le degré d'intensité du craving nécessaire pour que le critère soit rempli.…”
Section: Définition Du Cravingunclassified